Financial constraints and international trade with endogenous mode of competition - Bouët, Antoine; Vaubourg, Anne-Gaël (International Food Policy Research Institute, 2015)
The goal of this paper is to examine how financial constraints affect firms’ decisions to export when the mode of intra-sectoral competition is endogenous. We propose an extension of Neary and Tharakan’s (2012) model, in which firms resort to external funders to finance fixed export costs and investments in production capacities. We assume that sectors differ in financial constraint and that the cost of capital increases with the level of financial constraint. We first show that less financially vulnerable sectors are more likely to export. On the one hand, a high level of financial health allows firms to finance fixed export costs at a lower interest rate. On the other hand, financial health reduces the cost of investing in capacities, allowing firms to adopt a Cournot (rather than a Bertrand) pricing scheme and generate a high duopoly profit. We also exhibit a new transmission channel of financial crisis that affects both the extensive and intensive margins of trade. By increasing the cost of external finance, a financial shock increases the financial cost of exporting and reduces firms’ production capacities and exports (intensive margin). By making it more difficult to engage in a (highly profitable) Cournot pricing policy, such a shock also reduces firms’ duopoly profit and probability of exporting (extensive margin).